HAK-HAK WANITA DALAM HUKUM PERKAWINAN B.W. DITINJAU DARI SEGI HUKUM ISLAM - Marzuki Marzuki (Jurnal Penelitian Humaniora, 2000)
Abstract The research was aimed to know the woman rights in the Indonesian Civil Law (B.W) considered from Islamic law perceptive. The data of this content analysis study, were obtained from chapters of B.W. especially relating to the law of marriage. The results showed that in B.W. the rights given to the women were large enough. These were indicated of law marriage. The women rights in this marriage could be seen in this problems: (1)prerequisites for marriage, (2)preventive of marriage (3)rights and responsibilities of husband and wife, (4) unity and division of property, (5) agreement of marriage (6)dissolution of marriage (7)legal separation (of couple) (8)relationship between parents and children, (9)guardianship, (10)absence. The result of the analysis showed that many of these chapters suitable for Islamic law and few of these had not been suitable for it. Keywords: woman rights, marriage, Islamic law